Prevalence of cartilage erosion in canine patellar luxation and gene expression in affected joints - Boonsri B. (2017)
© 2016, Veteriner Fakultesi Dergisi. All rights reserved. The objectives of this study were to assess the prevalence of cartilage erosion in small dogs with patellar luxation (PL), and related osteoarthritis (OA)-related gene expression. In Study 1, 71 dogs were examined to determine risk factors associated with PL, including breed, age, weight, sex, and affected joint. In Study 2, a total of 39 dogs were divided into four groups: normal articular cartilage in the stifle joint (G1; n=5); PL without cartilage erosion (G2; n=11); PL with cartilage erosion (G3; n=14); and OA in the stifle (G4; n=9). Articular cartilage and synovial membranes were collected during surgical operations to correct PL. Real-time PCR was used to quantify the expression levels of 11 OA-related genes, including AGG, COL2A1, HAS-1, HAS-2, TIMP-1, MMP-3, IL-1β, TNF-α, IFN-γ, COX-1, and COX-2, with GAPDH used as a reference gene. From Study 1, it was found that the risk factors related with cartilage erosion lesion were age, sex, and PL grade (all variables showed P < 0.05). From Study 2, it was demonstrated that PL with or without cartilage erosion expressed pro-inflammatory cytokines and enzymes; some biomolecules were up regulated (IL-1β, MMP-3, AGG, TIMP-1) but some were down regulated (COL2A1, HAS-2, COX-1, COX-2). This expression was the difference between the articular cartilage and the synovial membrane; however, the expression of genes from PL with cartilage erosion was observed to be similar to that of OA. From our results, it can be concluded that PL can develop into secondary OA due to an increase of IL-1β in cartilage and synovial membrane.